The Impact of Parental Job Security on Children's Health - Ainoa Aparicio Fenoll; Pablo Fernandez-Baldor Laporta; Judit Vall Castello (Institute of Labor Economics (IZA), 2025)
Dual labor markets are characterized by a group of workers with permanent jobs and a stable income source and another group with short-term contracts who suffer from income uncertainty and employment volatility. These differences in job security translate into several spheres of these workers' lives, with potential implications for families' well-being. This paper analyzes the causal effect of parental job security on children's health. To address endogeneity, we exploit a reform that incentivized secure labor contracts for young (under 30) and female workers in Spain by reducing payroll taxes paid by employers. Using data from several waves of the Spanish National Health Survey and combining Instrumental Variables and Differences-in-Differences methods, we find that having a secure labor contract increases the probability that children are in good or very good health by 20%. We also document some mechanisms, such as reductions in children's accidents, increases in the frequency of physical activity, and a more protein-intense diet.
Keywords: I14; I12; J41; 330; job security; children's health